1130 White matter lesions in familial Alzheimer's disease: evidence for influence of mutation position on amyloid angiopathy?. Issue 3 (9th February 2012) - Ryan, N; Biessels, G; Bastos-Leite, A; Beck, J; Mead, S; Morris, H; Schott, J M; Rossor, M N; Fox, N C
Abstract : Background: Pathological studies show more prominent cerebral amyloid angiopathy (CAA) in Presenilin (PS1) mutations after codon 200 and APP mutations within the amyloid-β coding domain. We investigated whether mutation site influences the degree and location of white matter hyperintensities (WMH) on MRI. Methods: 52 FAD patients with mutations in APP (13) or PS1 (18 pre-, 21 post-codon 200) and 25 controls underwent MRI. WMH were visually rated using the age- related white matter change (ARWMC) scale. Rank-sum tests were used to assess group differences. Results: The PS1 post-200 group had a higher median total ARWMC score (3) than the pre-200 group (0, p=0.013) and controls (0, p=0.005). This was driven by an increased parieto-occipital ARWMC score. Mean disease onset-age was higher in the post- compared to pre-200 PS1 group (46.7 vs 39.2 yrs, p=0.0006). There was no difference in ARWMC score between controls and the pre-200 or APP cohort. The only APP intradomain mutation subject (A692G, Flemish) had a disproportionately high total ARWMC score (14) compared to the APP group median (0). Conclusion: The PS1 post-200 group had more severe WMH and a later age at onset than PS1 pre-200. The increased, predominantly parieto-occipital, WMH most likely represent CAA given the subjects' young age and lack of comorbidities. Study of the differential influence of FAD mutations can inform our understanding of AD pathophysiology, with potentially important implications for clinical trials.